Effect of Fermentation Time and Starbio Bioactivator Type and Local Microorganism (MOL) “Ginta” on The Nutritional Quality of Cassava Tuber Skin (Manihot Utilisima) - Bahria Nasution; Hasnudi .; Nurzainah Ginting; Yunilas .; Hamdan . (Jurnal Peternakan Integratif, 2018)
Abstract. BAHRIA NASUTION, 2018. "The Influence of Old Fermentation And Types Of Starbio Bioactivators And Local Microorganisms (MOL)" Ginta "Against Quality Nutritional Skin Cassava Bulbs (Manihot Utilisima). Guided by HASNUDI and NURZAINAH GINTING. The aim of this research is to know the nutrient content of cassava tuber skin waste (Manihot utilisima) fermented with starbio bioactivator type and local microorganism (MOL) "ginta". This research was conducted at Nutrition Research Lab for Nutritional Research on Goat Cut Sei Putih, from July to August 2017. The design used in this study was a complete randomized design (RAL) patterned 3x3 pattern with 3 replications. Factor I is fermentation starbio, fermentation of local microorganism (ginta), fermentation starbio + local microorganism (MOL) "ginta". Factor II is the fermentation length of 6.10 and 14 days. The parameters studied were water content, crude protein, crude fiber, ash content, crude fat, BETN. The result of bioactivator type research gave a very significant (P <0,01) to water content, crude protein, crude fiber and BETN of fermented cassava peel. The duration of fermentation had a very significant effect (P <0.01) on crude protein and lower ash, coarse, and coarse fat. The conclusion of fermentation using starbio can increase the crude protein, BETN and lower crude fiber, and ash content. Keywords : Cassava peel, fermentation, starbio, Bioactivator,”Ginta” Local Migroorganisms.